Blessed? A critical analysis of salvation in Denise Ackermann that portrays human flourishing as liberation, grace and the goodness of life - Marais, Nadia (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
Happiness and human flourishing has increasingly become a theological research focus in a variety of theological disciplines, including systematic theology (cf Charry, 2012), practical theology (cf Long, 2012) and biblical theology (cf Strawn, 2012). In systematic theology the focus of such research often is often creation, salvation and eschatology. The doctrine of salvation has particularly interesting (including etymological) connections with the notions of well-being and health. This paper, which forms part of PhD research on human flourishing, proposes to do a critical analysis of renowned Circle theologian Denise Ackermann’s understanding of salvation, since (1) feminist theology (and feminist theologians) has a particular concern for the ‘flourishing of all’, and (2) African theological voices on human flourishing should contribute to the emerging theological thinking on human flourishing. In this paper, it will be argued that salvation in Ackermann’s thought is infused with the vision for ‘abundant life for all’, which culminates with the notion of ‘blessing’.